Drug Resistance among Pulmonary Tuberculosis Patients in Calabar, Nigeria - Akaninyene Otu; Victor Umoh; Abdulrazak Habib; Soter Ameh; Lovett Lawson; Victor Ansa (Pulmonary Medicine)
Background. This study aimed to determine the pattern of drug susceptibility to first-line drugs among pulmonary TB patients in two hospitals in Calabar, Nigeria. Methods. This was a descriptive cross-sectional study carried out between February 2011 and April 2012. Sputum samples from consecutive TB patients in Calabar were subjected to culture on Lowenstein-Jensen (LJ) slopes followed by drug susceptibility testing (DST). The DST was performed on LJ medium by the proportion method. Results. Forty-two of the 100 Mycobacterium tuberculosis strains were found to be resistant to at least one drug. Resistance to only one drug (monoresistance) was found in 17 patients. No strains with monoresistance to rifampicin were found. Resistance to two drugs was found in 22 patients, while one patient was resistant to both three and four drugs. MDR TB was seen in 4% (4/100). The independent variables of HIV serology and sex were not significantly associated with resistance (P>0.05). Conclusion. There was a high prevalence of anti-TB drug resistance in Calabar.